REALISME DALAM KEBIJAKAN PENOLAKAN PENGUNGSI DAN MIGRAN OLEH HUNGARIA TAHUN 2015-2018 - Angga Nurdin Rachmat (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2020)
Refugees and migrants became a big problem in Europe after World War II, this time refugees came from Middle East cause of recent conflict in the region. Hungary, geographically is the country became a gateway for refugees and migrants coming from the Middle East to go to Western and Northern European countries. Hungary has become a party to the 1951 Refugee Convention and 1967 Protocol which has the mandate to carry out the protection and fulfillment of the rights of refugees who come to their territory, especially in this case Hungary is serve as a transit country. However, the facts that occur are Hungary's refusal of the presence of refugees by issuing a series of policies that are considered controversial and inviting criticism from the European Union and other European countries. Referring to the reality, this study attempt to explain the reasons behind Hungary's rejection of refugees and migrants from the Middle East by the realism perspective. This research was conducted with a qualitative approach where data were collected through interviews and literature studies. This research found that policies issued by Hungary are based on national interests which are the basis of consideration used by a country in making policies according to the view of realism. The national interest is related to the interests of core values, middle range objectives and long range goals that want to be maintained or protected when faced with the arrival of refugees and migrants to Hungary.